Physical modelling in geotechnics : proceedings of the 8th International Conference on Physical Modelling in Geotechnics 2014 (ICPMG 2014), Perth, Australia, 14-17 January 2014 /: proceedings of the 8th International Conference on Physical Modelling in Geotechnics 2014 (ICPMG 2014), Perth, Australia, 14-17 January 2014. ([2014]) - Unknown
No abstract available